PENGARUH KEPATUHAN PENGGUNAAN SUPLEMEN KALSIUM TERHADAP TEKANAN DARAH PADA PASIEN IBU HAMIL DI PUSKESMAS KECAMATAN KOJA JAKARTA UTARA TAHUN 2017 - Hadi Nugroho; Shomadiyah Ayu Masturoh; Ritha Widya Pertiwi (Jurnal Kesehatan STIKes IMC Bintaro, 2020)
Background : Based on Survei Demografi dan Kesehatan Indonesia (SDKI) 2012, there are 359 of 100000 live births from maternal mortality. It is caused by bleeding, hypertension, infection, abortion, prolonged partus, and other illnesses. One of many efforts to decrease the blood pressure is by giving calcium supplement. The main determinant of the effectiveness of the medical treatment in hypertension is obedience. Objective : This study aims to know the effect of obedience in consuming calcium supplement on blood pressure in pregnant women. Method : The method of this study is using observation with cohort retrospective design. The sample of this study is 88 pregnant women who consumed calcium supplement. They can communicate and they live in Koja Subdistrict’s local government clinic area. Result : The result of the study shows that there is no significant effect of obedience in consuming pregnant women’s calcium supplement on blood pressure (p > 0.05). Conclusion : The conclusion of this study is obedience in consuming calcium supplement on pregnant women does not show the significant effect on blood pressure.